Dual‐Functional Small Molecules for Generating an Efficient Cytochrome P450BM3 Peroxygenase. (30th March 2018) - Ma, Nana; Chen, Zhifeng; Chen, Jie; Chen, Jingfei; Wang, Cong; Zhou, Haifeng; Yao, Lishan; Shoji, Osami; Watanabe, Yoshihito; Cong, Zhiqi
Abstract: We report a unique strategy for the development of a H2 O2 ‐dependent cytochrome P450BM3 system, which catalyzes the monooxygenation of non‐native substrates with the assistance of dual‐functional small molecules (DFSMs), such as N ‐(ω‐imidazolyl fatty acyl)‐l ‐amino acids. The acyl amino acid group of DFSM is responsible for bounding to enzyme as an anchoring group, while the imidazolyl group plays the role of general acid–base catalyst in the activation of H2 O2 . This system affords the best peroxygenase activity for the epoxidation of styrene, sulfoxidation of thioanisole, and hydroxylation of ethylbenzene among those P450–H2 O2 system previously reported. This work provides the first example of the activation of the normally H2 O2 ‐inert P450s through the introduction of an exogenous small molecule. This approach improves the potential use of P450s in organic synthesis as it avoids the expensive consumption of the reduced nicotinamide cofactor NAD(P)H and its dependent electron transport system. This introduces a promising approach for exploiting enzyme activity and function based on direct chemical intervention in the catalytic process.